ATTACHMENT STYLE QUESTIOOAIRE IN UKRAINIAN LANGUAGE - Valeriа Kuchyna (World Science, 2025)
The article provides an overview of the results of the adaptation of a psychodiagnostic tool for measuring attachment styles into Ukrainian language. The OCП-22 (ukr) Attachment Style Questionnaire was adapted from the English version of the Attachment Style Questionnaire (ASQ) by Van Oudenhoven, Hofstra, and Bakker (2003), which was originally published in German. The new psychodiagnostic tool allows to determine the dominant attachment style among the main four domains: secure, anxious, avoidant, and disorganized. During the adaptation, all the necessary stages of the procedure were carried out, including the following: descriptive analysis of the distribution, reliability testing of the scales (Cronbach’s α and Macdonald’s Ω), exploratory analysis of the factor structure with its correlations between factors, and the confirmatory stage of checking the quality and fit of the model with the construction of its path diagram. It was not possible to conduct a competitive validity analysis due to the lack of adapted and available Ukrainian-language psychodiagnostic instruments for measuring attachment styles. We evaluated the test norms, described the features of the methodology’s structure and work with some items for further research. The Appendix presents the methodology itself, keys, and formulas for calculating the results. The internal consistency assessment of the scales showed a reliable level of coefficients. The survey sample consisted of 467 respondents. The OSP-22 questionnaire consists of 22 questions.